PENGARUH REWARD DAN EMPLOYEE ENGAGEMENT TERHADAP KINERJA KARYAWAN PT. CATUR SENTOSA ANUGERAH Tbk BANDUNG - Rosa Maria Rostandi, - (2021)
In order to create high employee performance, a company need to optimaly improve their performance and be able to use their potential humans and resourses. This study aim to found out an overview of reward, employee engagement and employee performance and also the effect of reward and employee engagement towards employee performance at PT. Catur Sentosa Anugerah, Tbk In Bandung. This study is using desciptive and verificative research method with quantitative approach and a saturated sampel. Respondent of this study is all employees of PT. Catur Sentosa Anugerah, Tbk with 100 samples. The analysis tehcnique used in this study is multiple linier regression using SPSS 25.0 computer software tool. t-statistics is used to testing Hypothesis, While R² is used to determine how the influence of the independent variables together on the dependent variable. This study showed that reward, employee engagement and employee performance at PT. Catur Sentosa Anugerah, Tbk In Bandung were in high category. the result of statistical analysis showed that reward and employee enggament simultaneously has positive and significant effect towards employee performance. Partially, Reward and employee engagement also has positive and significat effect towards employee performance at PT. Catur Sentosa Anugerah, Tbk In Bandung.